FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP MANAJEMEN LABA - Gracia, Jefta; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2024)
This journal contains the information of the effect about how profitability, leverage, institusional ownership, managerial ownership, and sales growth affects earnings management in manufacturing companies listed in the Indonesia's Stock Exchange between 2018-2020 period. This research used 29 manufacturing company that filtered by using purposive sampling method for a total 196 manufacturing company in 3 years span. The results of this research showed that there’s a negative and significant effect of sales growth on earnings management, on the other side, results of profitability, leverage, institusional ownership, managerial ownership contain no significant effcet on earnings management.